2003
DOI: 10.1007/s00424-003-1181-1
|View full text |Cite
|
Sign up to set email alerts
|

An MR-compatible device for the in situ assessment of isometric contractile performance of mouse hind-limb ankle flexors

Abstract: The goal of the present study was to develop and evaluate an isometric dynamometer for measuring mouse ankle flexor torque after electric stimulation of the nerve. The dynamometer was to be used within an magnetic resonance (MR) apparatus and should require minimal surgical intervention. To quantify the effect of the magnetic field on contractile parameters, measurements were performed both outside and inside the MR apparatus. The effect of magnetic field gradient switching that accompanies rapid MR scanning w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
2
6
0
Order By: Relevance
“…where B 0 =~0.2-0.4 mT) demonstrated identical slopes with a difference for the Y-intercepts between the two testing conditions. In agreement with a previous study (11), these findings indicated that the magnetic field led to changes in the force offset, reaching~100 mN, that did not influence the reliability of the measured force production. Additionally, when considering the ergometer as a whole (i.e.…”
Section: Mechanical Performance Of the Ergometersupporting
confidence: 92%
See 1 more Smart Citation
“…where B 0 =~0.2-0.4 mT) demonstrated identical slopes with a difference for the Y-intercepts between the two testing conditions. In agreement with a previous study (11), these findings indicated that the magnetic field led to changes in the force offset, reaching~100 mN, that did not influence the reliability of the measured force production. Additionally, when considering the ergometer as a whole (i.e.…”
Section: Mechanical Performance Of the Ergometersupporting
confidence: 92%
“…r 2 > 0.99) with a very slight hysteresis (i.e. ~2%) which is in line with a previous device compatible with a high‐field MR system . In order to further illustrate the robustness of our ergometer, we performed two sets of force measurements during a standardized stimulation protocol over a 1‐week period.…”
Section: Discussionsupporting
confidence: 81%
“…Experiments were performed on female C57BL/6 mice (23 ± 2 g; mean ± SD) that were positioned in an MRI‐compatible cradle equipped with a torque transducer (24). The mice were anesthetized with isoflurane (Schering‐Plough, Animal Health, Maarssen, The Netherlands), 1.0–1.5% in air, with a flow rate of 0.4 l/min, controlled by a flow meter system (UNO, Zevenaar, The Netherlands).…”
Section: Methodsmentioning
confidence: 99%
“…Experiments ( N = 6) were performed on male C57BL/6 mice (26.5 ± 1.4 g, mean ± SD) that were positioned in an MRI‐compatible device (19). The mice were anesthetized with isoflurane (Schering‐Plough, Animal Health, Maarssen, The Netherlands), 1.0–1.5% in air, with a flow rate of 0.4 l/min, controlled by a flow meter system (UNO, Zevenaar, The Netherlands).…”
Section: Methodsmentioning
confidence: 99%